Analisis Kebutuhan Pembelajaran Tematik di SDN Kalideres 06 Pagi - Magdalena, Ina; Sartika, Devi; Humaerah, Humaerah; Agusta, Farhan Ardhya (Lembaga Yasin AlSys, 2021)
Needs Analysis is a method used to identify the needs needed by students so that educators are able to meet these needs. Through the right steps, problems that cover the thematic learning will be resolved. This study aims to determine the needs of educators and students, especially elementary schools in thematic learning. This is a survey research using descriptive methods to collect data. The results showed that students' needs related to learning methods and media were very much needed, if a teacher did not pay attention to the needs of students in learning, students would feel bored and have no clear learning goals, so that teaching and learning activities were not optimal. With this research, it is hoped that teachers will be able to analyze learning needs before teaching and learning activities are held, this is to minimize the occurrence of problems in learning elementary schools.